Effectiveness of Warm Water Foot Bath Therapy on Quality of Sleep among Elderly - Arati Raut; Gunjan Morade; Dnyaneshwari More; Sanjivani Mune; Pratiksha Munjewar; Mayuri Mute (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Insomnia is a subjective complaint of inadequate night-time sleep. It is the most prevalentsleep disorder identified by older people.1Depression, anxiety, and reduced cognitive function have been linked with severe lack of sleep. Poor sleepquality in the elderly reduces the quality of life, but sadly the most elder people do not report sleep problemsunless expressly requested. Warm water foot bath provides a better sleep at night, as it calm downs andrelaxes the body and mind. This works by increasing the body temperature slightly and after 15 minutes thisstarts to drop gradually. This may indirectly encourage sleep. Gradual decrease in body temperature makesus feel drowsy and so we feel better prepared for sleep. A warm water foot bath also diverts some blood fromthe head to lower parts of the body, decreases brain activity and mimics the state of pre-sleep.2 We wanted todetermine the effectiveness of warm water foot bath therapy on quality of sleep among elderly.Methods: In this study the 60 older adults are selected based on inclusion criteria and were assigned toexperimental and control group alternatively. The experimental group composed of 30 elder people andcontrol group contained 30 elder people. The researcher developed rapport with older people receiving warmfootbath and explained the benefits of intervention. The day we began the data collection, the demographicdata and pretest took from elder people of experimental group and control group. On the next day, warmfootbath was given by the researcher with duration of 15 – 20 minutes for five consecutive days in olderpeople of experimental group. On the other hand, routine work is maintained in control group. Posttest wasdone on sixth day for both experimental and control group to assess the sleep quality among elderly by usingGroningen Sleep Quality Scale.4Results: Findings shows that 25 sample (83.33 %) had undisturbed sleep at night, 5 (16.67 %) had disturbedsleep at night using warm water footbath therapy and none of them had poor sleep at night. The minimumscore was 2 and the maximum score was 7 and the mean score was 4.23 ± 1.30 with a mean percentage of30.2 %. There significant association between qualities of sleeps and age group.Conclusions: The significant difference between preexisting sleeping quality and effectiveness footbathinterpreting effective quality of sleep using warm water footbath therapy among elderly. Mean value ofpreexisting sleeping quality is 8.93 and effectiveness of footbath therapy is 4.23 and standard deviationvalue of preexisting sleeping quality is 0.828 and effectiveness of footbath is 1.305. The calculated t-valueis 14.75 and p-value is 0.000. Hence it is statistically interpreted that the effectiveness of footbath therapyamong elderly was effective